Synergistic Effects of Vermicompost and Biochar Amendments on Soil Fertility and Wheat Productivity in Bangladesh Floodplain Soils - Ahmed Khairul Hasan; Shams Shaila Islam; Marina Jahan; Sinthia Afsana Kheya; Md. Romij Uddin; Md. Shafiqul Islam; Thanet Khomphet (Scientifica)
Biochar is gaining importance due to its potential to enhance soil health, crop yield, and quality. It may also promote more sustainable farming methods. This study evaluated the combined effects of biochar, vermicompost, and inorganic fertilizers on soil characteristics, growth, and yield in wheat. Ten different treatments were applied to wheat (cultivar BARI Gom-33). The tallest plants, highest total dry weight, and largest leaf area index were observed in plots where chemical fertilizers, rice husk biochar, poultry manure, and vermicompost were applied together. At harvest, the treatment containing 1/4 recommended fertilizer dose (RFD) + 1/4 poultry manure biochar + 1/4 rice husk biochar + 1/4 vermicompost produced the best yield and yield-contributing factors. The combination of biochar, vermicompost, and inorganic fertilizers increased grain production by 43.23%–79.48% compared with the control. These treatments also improved soil health by increasing available phosphorus, organic matter, carbon-to-nitrogen ratio, and organic carbon. In conclusion, the combined application of 1/4 RFD, 1/4 poultry manure biochar, 1/4 rice husk biochar, and 1/4 vermicompost can replace the sole use of chemical fertilizers and serve as a key component for sustainable crop production.